MATHEMATICAL SIMULATION OF CONCURRENT TWO-SIDED LENS PROCESSING - A. S. Kozeruk; E. O. Lapteva; I. P. Filonov; M. I. Filonova (Наука и техника)
The purpose of the paper is to modernize technology for obtaining high-accuracy lenses with fine centre. Presently their operating surfaces are fixed  to an accessory with the help of adhesive substance that leads to elastic deformation in glass and causes local errors in lens parts.A mathematical model for concurrent two-sided processing of high-accuracy optical parts with spherical surfaces has been developed in the paper. The paper presents analytical expressions that permit to calculate sliding speed at any point on the processed spherical surface depending on type and value of technological equipment settings. Calculation of parameter Q = Pv in a diametric section of the convexo-concave lens has been carried out while using these expressions together with functional dependence of pressure on contact zone еarea of tool and part bedding surfaces.Theoretical and experimental investigations have been carried out with the purpose to study changes in Q parameter according to the processed lens surface for various setting parameters of the technological equipment and their optimum values ensuring preferential stock removal in the central or boundary part zone or uniform distribution of the removal along the whole processed surface have been determined in the paper.The paper proposes a machine tool scheme for concurrent two-sided grinding and polishing of lenses while fixing their side (cylindrical) surface. Machine tool kinematics makes it possible flexibly and within wide limits to change its setting parameters  that significantly facilitates the control of form-building process of parts with highly-precise spherical surfaces.Methodology for investigations presupposes the following: mathematical simulation of highly-precise spherical surface form-building process under conditions of forced closing, execution of numerical and experimental studies.